Konsep Humanisme Ditinjau dari Perspektif Pendidikan Islam - Eka Nilam Safitri; Ashif Az-Zafi (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Researchers conducted this research because they deperted from education to instill the concept of humanism in their daily lives so that a lot of the problems that occurred in real life began with the bullying case, disrespect for the differences that occur, blaspheming each other on social media. This study aim to determine how Islamic education views the concept of humanism. The method the author uses to make this research is to refer to pepper the method or library research. Based on the discussion, it can be concluded that the concept of humanism in the view of Islamic education that humanism exists in the alquran and in Islamic education concept of humanism aims to seek the blessing of god with the feedom to develop religious knowledge and general knowledge for the benefit of the people